Legitimacy and reputation of organizations: Their relationship with management systems and financial performance - Orviz Martínez, Natalia; Cuervo Carabel, Tatiana; Castillo Feito, Cristina del (Organizational Legitimacy: Challenges and Opportunities for Businesses and Institutions, 2020)
Legitimacy and reputation are intangible assets of growing importance for the survival of organizations, so it is very important to develop strategies that improve these assets. In addition, the implementation of management systems based on ISO standards has had a strong development worldwide since their emergence. The main objective of this research is to analyse whether the adherence to ISO 9001 and ISO 14001 and the implementation of an integrated management system (IMS) of both standards can have a positive effect on the legitimacy and reputation of organizations. On the other hand, a complementary objective is to contrast the influence of these intangible assets on their financial performance. For this purpose, the companies of the IBEX-35 stock index were selected, using structural modelling with PLS through SmartPLS software. The results obtained show that the certification in these ISO standards has a positive influence on the legitimacy and reputation of the organizations that implement them; on the other hand, the establishment of an IMS for both standards has a positive effect on the legitimacy of companies, but it does not have this effect on their reputation. There is also a positive relationship of the two intangible assets on the financial performance of organizations.
Capítulo del libro "Organizational Legitimacy: Challenges and Opportunities for Businesses and Institutions"
Keywords: 14001 standard; 9001 standard; environment; financial performance; integrated management system (IMS); legitimacy; management systems; quality; reputation; Scopus(2)